Spazi pedagogici nell’incontro con l’altro - Lombardi, Maria Grazia (Studi sulla Formazione/Open Journal of Education, 2017)
This work analyzes the theme of intercultural education through the pedagogical category of the possible utopia which, in the intercultural educational reflection, necessarily refers to the idea of pedagogical space. In this direction the reflections move from a fundamental question. What is the pedagogical space of intercultural education? So what is the educational space of the meeting with each other? It is through this question that work moves from the hypothesis that pedagogical spaces in the meeting with each other can create that one and only humanity, ped-agogically meant  uniqueness, as the uniqueness of human rights.